2019
DOI: 10.9734/mrji/2019/v29i330164
|View full text |Cite
|
Sign up to set email alerts
|

Bio-activities of Tetracycline and Algae Food Supplement Algo-Bio® on Escherichia coli Antimicrobial Resistance Isolated from Piglet’s Intestinal Flora

Abstract: Aims: This study aimed at evaluating the effect of Algo-Bio® use on Escherichia coli resistance strains isolated from piglets intestinal flora. Study Design: Bacteriological study. Place and Duration of Study: Laboratory of the National Reference Center for antibiotics at Institute Pasteur Côte d’Ivoire, between March 2018 and June 2018. Methodology: A breeding of three batches of two piglets was carried out, then treatments with tetracycline and Algo-Bio® were administered to them. Enterobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…A recent study in piglets also showed that supplementing a seaweed product in drinking water (Algo-Bio ® ) decreased the Enterobacteria resistance rate to tetracycline [104]. In addition, in piglets treated with a seaweed supplement, the antibiotic susceptibility test showed a high sensitivity of Escherichia coli to imipenem, amikacin, and netilmicin with low chloramphenicol resistance.…”
Section: Seaweed Polysaccharides As Prebiotics In Post Weaning Pigletsmentioning
confidence: 92%
“…A recent study in piglets also showed that supplementing a seaweed product in drinking water (Algo-Bio ® ) decreased the Enterobacteria resistance rate to tetracycline [104]. In addition, in piglets treated with a seaweed supplement, the antibiotic susceptibility test showed a high sensitivity of Escherichia coli to imipenem, amikacin, and netilmicin with low chloramphenicol resistance.…”
Section: Seaweed Polysaccharides As Prebiotics In Post Weaning Pigletsmentioning
confidence: 92%